2018
DOI: 10.21138/bage.2532
|View full text |Cite
|
Sign up to set email alerts
|

Impacto del calentamiento global en la distribución y supervivencia del pinsapo (Serranía de Ronda)

Abstract: Tras la retirada de los hielos glaciares del Cuaternario, los abetos se replegaron hacia el norte o ascendieron en altitud hacia las montañas. Escindido del tronco común del abeto primigenio, Abies pinsapo persiste como especie relicta y endémica de la Serranía de Ronda, y una de las reliquias más meridionales de la aciculisilva. En este trabajo, desarrollamos un ensamblaje de modelos de nicho ecológico del pinsapo calibrados con datos actuales y proyectados hasta el horizonte 2100 según los escenarios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 101 publications
3
8
0
2
Order By: Relevance
“…Benefiting from future climate change, a large number of currently unoccupied areas in southern and western Sichuan will be potentially suitable for A. recurvata (Figure 4a). On the other hand, Liu et al (2018) found at the genus level that the reduction in distribution area under the RCP 8.5 scenario was significantly higher than that under the RCP4.5 scenario. Although our projections for most species were consistent with this general finding, for A. squamata, the net loss of CSAs under the RCP 4.5 scenario was predicted to be twice as large as that under the RCP 8.5 scenario (Figure 5a).…”
Section: Partial Migrationmentioning
confidence: 75%
See 4 more Smart Citations
“…Benefiting from future climate change, a large number of currently unoccupied areas in southern and western Sichuan will be potentially suitable for A. recurvata (Figure 4a). On the other hand, Liu et al (2018) found at the genus level that the reduction in distribution area under the RCP 8.5 scenario was significantly higher than that under the RCP4.5 scenario. Although our projections for most species were consistent with this general finding, for A. squamata, the net loss of CSAs under the RCP 4.5 scenario was predicted to be twice as large as that under the RCP 8.5 scenario (Figure 5a).…”
Section: Partial Migrationmentioning
confidence: 75%
“…Generally, isothermality is regarded as the most decisive factor for firs in the MSWC (Chhetri et al, 2018;Liu et al, 2018).…”
Section: Key Factors Shaping Species Distributionsmentioning
confidence: 99%
See 3 more Smart Citations